2005
DOI: 10.2310/6350.2005.31222
|View full text |Cite
|
Sign up to set email alerts
|

Microcystic Adnexal Carcinoma Involving a Large Portion of the Face: When Is Surgery Not Reasonable?

Abstract: Mohs surgery should be the treatment of choice for this tumor; however, when extirpation entails sufficiently large morbidity, given the low rate of metastases and mortality, observation is a reasonable alternative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Chemotherapy might be useful in patients with widespread disease who have no other treatment options, but it is not first-line treatment (Eisen, 2005).…”
Section: Histological Features Of Macmentioning
confidence: 99%
“…Chemotherapy might be useful in patients with widespread disease who have no other treatment options, but it is not first-line treatment (Eisen, 2005).…”
Section: Histological Features Of Macmentioning
confidence: 99%
“…These have usually had extensive locoregional disease, and treatment has usually been unsuccessful [ 29 ] . In one patient, the tumor is even thought to have recurred in a more extensive and aggressive form 6 months after primary radiotherapy [ 42 ] .…”
Section: Treatmentmentioning
confidence: 99%
“…In a third study [ 28 ] , there was a history of radiotherapy in 2 out of 13 patients, of whom one was also a renal transplant patient on immunosuppression. In a review [ 29 ] of 274 published cases of MAC, a history of radiation exposure is reported to have preceded development of the tumor in 14 of 84 patients in whom a history was available, an incidence of 19.5%.…”
Section: Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations